On some sublattices of regular operators on Banach lattices - Nouira, R.; Aqzzouz, B. (Methods of Functional Analysis and Topology, 2008)
We give some sufficient conditions under which the linear span of positive compact (resp. Dunford-Pettis, weakly compact, AM-compact) operators cannot be a vector lattice without being a sublattice of the order complete vector lattice of all regular operators. Also, some interesting consequences are obtained.